Spatial And Temporal Variability Of Heavy Elements Of Trocar Water In The Mada'in District (Journal of the College of Basic Education, 2024)
The aim of this study is to evaluate and study the heavy elements in the water trolls of Mada'in district to find out their suitability for agricultural investment, as the aim of the study, especially after the recent water scarcity, especially the central and southern regions, to make the best possible use of all available water resources to meet basic needs.Where heavy elements such as lead, cadmium, copper, boron and nickel were addressed, the results showed that there is a temporal and spatial variation in the values of the results, some of them with high percentages, such as the contact point of trocars, and some with low percentages due to the lack of dumping pollutants in it.